Spike Timing Neural Model of Motion Perception and Decision Making - Koprinkova-Hristova, Petia D.; Bocheva, Nadejda; Nedelcheva, Simona; Stefanova, Mirsolava (Frontiers in Computational Neuroscience, 2019)
The paper presents a hierarchical spike timing neural network model developed in NEST simulator aimed to reproduce human decision making in simplified simulated visual navigation tasks. It includes multiple layers starting from retina photoreceptors and retinal ganglion cells (RGC) via thalamic relay including lateral geniculate nucleus (LGN), thalamic reticular nucleus (TRN) and interneurons (IN) mediating connections to the higher brain areas – visual cortex (V1), middle temporal (MT) and medial superior temporal (MTS) areas, involved in dorsal pathway processing of spatial and dynamic visual information. The last layer – lateral intraparietal cortex (LIP) – is responsible for decision making and organization of the subsequent motor response (saccade generation). We simulated two possible decision options having LIP layer with two sub-regions with mutual inhibitory connections whose increased firing rate corresponds to the perceptual decision about motor response – left or right saccade. Each stage of the model was tested by appropriately chosen stimuli corresponding to its selectivity to specific stimulus characteristics (orientation for V1, direction for MT and expansion/contraction movement templates for MST respectively). The overall model performance was tested with stimuli simulating optic flow patterns of forward self-motion on a linear trajectory to the left or to the right from straight ahead with a gaze in the direction of heading.